2021
DOI: 10.1029/2021gl094376
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic Mesoscale Eddy Depletion Catalyzed by Internal Waves

Abstract: The general circulation of the ocean is strongly constrained by the pathways that kinetic and available potential energy take from the basin-scale forces that inject them to centimeter scales, where they are depleted. To determine the ocean's response to future climate scenarios, these energy pathways, from forcing to dissipation, must be understood and quantified.Mesoscale eddies, with horizontal scales on the order of 100 km and timescales longer than many days, are well known as the dominant reservoir of ki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 67 publications
(84 reference statements)
6
38
0
Order By: Relevance
“…In light of the SWOT altimeter mission (Morrow et al, 2019;Torres et al, 2019), the di↵erence between the runs with tidal forcing and without (e.g. Figures 1 and 3) highlight the importance of tidal forcing in emulating the upcoming altimeter observations (Arbic et al, 2018;Barkan et al, 2021;Yu et al, 2021). -18-manuscript submitted to Geophysical Research Letters energy of the internal wavefield and stratification set to E0 = 6.3e 5 m 2 s 2 and N0 = 5.2e 3 s 1 , respectively (Garrett & Munk, 1975;Cairns & Williams, 1976;Müller et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of the SWOT altimeter mission (Morrow et al, 2019;Torres et al, 2019), the di↵erence between the runs with tidal forcing and without (e.g. Figures 1 and 3) highlight the importance of tidal forcing in emulating the upcoming altimeter observations (Arbic et al, 2018;Barkan et al, 2021;Yu et al, 2021). -18-manuscript submitted to Geophysical Research Letters energy of the internal wavefield and stratification set to E0 = 6.3e 5 m 2 s 2 and N0 = 5.2e 3 s 1 , respectively (Garrett & Munk, 1975;Cairns & Williams, 1976;Müller et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thomas & Daniel, 2021). From a theoretical standpoint, there are so far essentially two well known and documented energy transfer mechanisms from balanced motions to IGWs away from topography, namely the stimulated generation of a forward cascade of kinetic energy by nearinertial waves from balanced flows (Gertz & Straub, 2009;Rocha et al, 2018;Barkan et al, 2021) and the spontaneous generation of near-inertial waves from balanced flows (Nagai et al, 2015;Shakespeare & Hogg, 2017). In stimulated generation, near-inertial waves are first introduced by external forcing (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the interactions of NIWs with eddies and associated energy transfers are not a direct consequence of the chimney effect. It has recently been suggested that the presence of NIWs can result in a substantial reduction of mesoscale kinetic energy by stimulating a forward energy cascade at partially-balanced submesoscale fronts (Barkan et al, 2021).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…More recently, the inertial chimney effect of turbulent baroclinic quasi-geostrophic eddies was also demonstrated by under an idealized storm scenario, where they referred to this effect as 'inertial drainpipe'. Vic et al (2021) examined the association of mooring-measured near-inertial energy with altimetry-derived relative vorticity with a horizontal resolution of O(100 km) over the Mid-Atlantic Ridge, and showed that nearinertial energy is preferentially funneled down within anticyclonic flows. To our knowledge, observational assessment of the chimney effect down to the submesoscales (0.1-10 km) has not yet been performed.…”
Section: Introductionmentioning
confidence: 99%